مساهمة أساليب المعاملة الوالدية المدركة في ظهور الألكسثيميا دراسة ميدانية لمجموعة من النساء المصابات باضطرابات سيكوسوماتية بـ: بن يزقن ولاية غرداية. (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص:  تهدف الدراسة الكشف عن مدى مساهمة أساليب المعاملة الوالدية المدركة في ظهور الألكسثيميا لدى مجموعة من النساء المصابات باضطرابات سيكوسوماتية، وباستخدام المقاربة التكاملية "L’approche Intégratif "  وتطبيق الأدوات الآتية: مقياس كورنل، ومقياس أساليب المعاملة الوالدية المدركة لهدى كشرود وTAS20، وكذا المقابلة نصف الموجهة؛ على عينة تتكون من 03 نساء راشدت.توصلت النتائج إلى وجود مستوى مرتفع من الألكسثيميا، كما أن الأنماط السلبية المدركة لأساليب المعاملة الوالدية تؤدي إلى  اضطرابات علائقية ووجدانية واختلالات في الإدراك الانفعالي لدى مجموعة الدراسة.كلمات دالة : ألكسثيميا، اضطرابات سيكوسوماتية، أساليب والدية. تعبير انفعالي. Abstract- This study aims at revealing The study aims to reveal the extent of the contribution of perceptual parenting methods to the emergence of alexithymia in a group of women with psychosomatic disorders, by using the integrative approach "The Integrative Approach" and by applying the following tools: Hoda Kachroud and TAS20 Parenting Style Scale, as well as semi-structured interview; On a sample made up of 03 adult women.The results revealed a high level of alexithymia, and the perceived negative patterns of parenting styles lead to relationship and affective disturbances and imbalances in emotional perception among the study group.Key words: Alexithymia ; psychosomatic disorder  parental treatment ; Emotional expression